Students’ Metacognitive Skills in Solving Probability Investigation-Based Problem - Diantik, Dini Nur; Wulan, Eka Resti; Surur, Agus Miftakus (Al-Khawarizmi, 2022)
This study aims to describe the metacognitive abilities of students in solving opportunity problems with nuanced investigations based on the mathematical abilities of grade 12 students in one of the high schools in Kediri Regency, East Java, Indonesia. This research uses a descriptive type, with a qualitative approach. Data collection techniques in the form of giving tests with the think-aloud method and semi-structured interviews. The research instrument consisted of a problem test with investigative-based and interview guidelines. The research participants consisted of three grade 12 students each with high, medium, and low mathematical abilities. The results of this study indicate that at the stage of understanding the problem, metacognitive activity appears in the form of awareness and evaluation. However, the low participant was not able awareness in a good way and the medium participant was not doing a careful evaluation of the results. In the planning stage, the high and medium participants currently use regulation activities by thinking about the right strategy. Evaluation activities, such as believing in the effectiveness of the strategy and assessing the results appropriately. In the stage of implementing the plan, the high and medium participants are using regulation activities by monitoring the planned solutions properly. Evaluation activities are carried out with an appropriate assessment of each result. However, the opposite appeared for low participant in both previous stages. In the stage of looking back, evaluation activity appears in the form of assessing the suitability of answers to the context of the problem with investigative nuances, but no metacognitive activity was found in low participant.